APLIKASI JADWAL PERKULIAHAN DAN PELAYANAN DOSEN MENGAJAR DI BIRO ADMINISTRASI AKADEMIK UNIVERSITAS SAHID SURAKARTA - Radite Purwahana; Dwi Retnoningsih; Firdhaus Hari Saputro Al Haris (JURNAL GAUNG INFORMATIKA, 2017)
Until now, the activity of making lecture schedules, recaps lecturer teaching, teaching faculty and SK presence of lecturers teaching Sahid University Surakarta still done by semi-manual. The process is still semi manual and accuracy factors sometimes lead management generated less than perfect. Supported by the advanced technology of today's world, then how making lecture schedules, recaps lecturer teaching, teaching faculty and SK presensi teaching faculty should be addressed to follow along with the development of science and technology. This study aimed to establish Class Service System Sahid University Surakarta for ease of manufacture lecture schedules, recaps lecturer teaching, teaching faculty and SK presence of lecturers teaching. This system was written using the PHP programming language with UML as a model method, and using data collection techniques include interviews, observation, library research, and uses sequential analy sis Linear Model or Waterfall Model Class Service System Sahid University of Surakarta has been tested with a method WebQual to 30 respondents and produce final calculation value of 80.1%. Based on these results it can be concluded that Class Service System Sahid University Surakarta is good and deserves to be implemented at Sahid University of Surakarta